2009
DOI: 10.1128/jb.00703-09
|View full text |Cite
|
Sign up to set email alerts
|

CebR as a Master Regulator for Cellulose/Cellooligosaccharide Catabolism Affects Morphological Development in Streptomyces griseus

Abstract: Streptomyces griseus mutants exhibiting deficient glucose repression of ␤-galactosidase activity on lactosecontaining minimal medium supplemented with a high concentration of glucose were isolated. One of these mutants had a 12-bp deletion in cebR, which encodes a LacI/GalR family regulator. Disruption of cebR in the wild-type strain caused the same phenotype as the mutant, indicating that CebR is required for glucose repression of ␤-galactosidase activity. Recombinant CebR protein bound to a 14-bp inverted-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 49 publications
1
54
0
Order By: Relevance
“…The most common regulatory mechanism for bacterial cellulolytic systems involves a repressor. CebR is a classic repressor of several operons of the Streptomyces griseus cellulolytic system that responds to cellodextrins (11). The cellulase system of Thermobifida fusca is transcriptionally regulated by cellobiose induction mediated through CelR (15,22).…”
mentioning
confidence: 99%
“…The most common regulatory mechanism for bacterial cellulolytic systems involves a repressor. CebR is a classic repressor of several operons of the Streptomyces griseus cellulolytic system that responds to cellodextrins (11). The cellulase system of Thermobifida fusca is transcriptionally regulated by cellobiose induction mediated through CelR (15,22).…”
mentioning
confidence: 99%
“…3). A similar regulation of a LacI/GalR family regulator, namely, transcription from two independent promoters, an autoregulated promoter and another constitutive one, has also been reported in Streptomyces griseus CebR, a regulator of cellulose/cello-oligosaccharide catabolism (36).…”
Section: Discussionmentioning
confidence: 94%
“…It was strongly suggested that these gene products are secreted outside the cells as mature, active enzymes by digestion of the N-terminal signal peptides. In S. griseus, CebR, a regulatory protein for cellobiose/ cellooligosaccharide catabolism, binds to the CebR box, a 14-bp inverted repeat sequence (TGGGAGCGCTCCCT), to repress the transcription of the genes related to the catabolism [32]. The CebR box sequences were found upstream of the cel9A C , cel5A M , and cel12B M genes, suggesting that expression of these genes are regulated by CebR to be inducible by cellobiose in the C42 and M178 strains.…”
Section: Cloning and Nucleotide Sequencing Of Secretorymentioning
confidence: 99%